The effectiveness of mindfulness-based therapy on working memory indices in patients with hypertension: a randomized clinical trial - Fatemeh Rabipour; Seyed Davood Hosseininasab; Arsalan Salari (مجله علوم پزشکی فیض (پیوسته))
Background and Aim: Hypertension are an important risk factor for many diseases. Literature indicates different cognitive activities and executive functions, such as weaker working memory in hypertension patients compared to healthy. Therefore, the present study was conducted to determin the effectiveness of mindfulness-based therapy on working memory indicators of patients with hypertension. Methods: The present study was a double-blind randomized clinical trial, based on a pre- and post-test design and a two-month follow-up with a control group. The research population included all people with hypertension in Rasht city (north of Iran) who visited Heshmat Heart Hospital in 2021. From this population, 34 volunteers were selected by purposive sampling and randomly assigned to intervention and control groups. The tool used in this study was Kirchner's 1 and 2 BACK test (computerized version) and a mindfulness therapy was performed during 8 sessions of 120 minutes once a week for the intervention group. Results: Before the intervention in the pre-test, the mean working memory indices of the intervention group and the control group were not significantly different. At the end of the intervention in the post-test, the mean working memory indices of the intervention group (1-back, correct answers = 75.17, reaction time = 462.61; and 2-back, correct answers = 67, reaction time = 495.81) and the control group (1-back, correct answers=69/35, reaction time=617/75; and 2-back, correct answers=59/71, reaction time=663/56) were significantly different (P<0.0001). In other words, the therapy based on mindfulness was effective in improving working memory indices of patients with hypertension. Also, the outcome did not change in the follow-up phase in both groups, which indicates the stability of the therapy in the intervention group. Conclusion: Mindfulness therapy is effective on working memory indicators of patients with hypertension. Therefore, it is suggested that the mentioned intervention be used in medical centers to improve the cognitive activities of patients with hypertension, although it seems necessary to conduct more studies in this field.